Fetal Outcome in Unhooked Postdated Pregnancy - Mustafa, Fahmida Naz; Yasmin, Nahid; Afreen, Nasreen; Sattar, Kamrun; Nahar, Aftabun; Nahar, Nazmun (Journal of Dhaka Medical College, 2018)
Background: People always complain that previously almost all women used to have vaginal delivery, but they do not mention the fetal outcome, eg, the number of affected fetus and also intrauterine death or stillborn. The objective of our study was to see the fetal outcome among antenatally unbooked women with gestational age beyond EDD who came to hospital with labor pain and also to see the mode of delivery in these pregnancies. Method: It was an observational prospective study conducted in Daudkandi Upazilla Health Complex, Kumilla, from March , 2012 to May, 2012. Sampling procedure was consecutive sampling. A total number of 52 postdated pregnant women were enrolled in our study who came to hospital with labor pain. Result: The percentage of vaginal delivery in postdated pregnancy was 80.77% and the percentage of cesarean delivery was 19.23% . Fetal outcome was good in 76.92%, baby was asphyxiated in 19.23% , baby was stillborn in 3.85% women. Conclusion: Though vaginal delivery rate is high in women with antenatally unbooked postdated pregnancy with spontaneous onset of labour pain , but the fetal outcome is not good. The women who are crossing EDD must undergo careful fetal monitoring to have more vaginal delivery with good fetal outcome. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 47-50